Cultural Capital as Class Strength and Gendered Educational Choices of Chinese Female Students in the United Kingdom - Zhang, Siqi; Tang, Xiaoqing (Frontiers in Psychology, 2021)
The present qualitative study analyzes how cultural capital, gender, class, and family involvement impact Chinese female students’ aspirations of studying in the United Kingdom. We investigated how these factors facilitate or limit female students’ choice of study destination, as well as choices of subject and program. Data were gathered through participant observation and semi-structured interviews in a British university. A total of 25 young Chinese female students from different subject areas took part in the semi-structured interviews. Out of those, five students are undergraduates, 11 are taught master’s students, and the other nine students are doctoral candidates. Most of the undergraduates and postgraduates are from middle-class families, while some of the Ph.D. students are from working-class families. The results of the content analysis were examined in light of gender and cultural capital theory. It was found that although there exist differences within the middle-class families regarding the possession of cultural capital, many female students from middle-class families obtained high levels of cultural capital, and these students usually internalized the idea of pursuing a place in the United Kingdom’s tertiary education system as a way of enhancing women’s competency in future job markets. Furthermore, compared with working-class students, many respondents’ choice of subject and program was highly gendered, as their families expect them to live a feminine life by choosing “appropriate” feminine subjects. Therefore, despite having the privilege to study abroad, female middle-class students’ educational choices are still constrained by gender and class.